Stereological analysis of capillaries in thick slice of skeletal muscle - Čebašek, Vita (Anali PAZU, 2022)
Stereological analysis of the thick cross sections of fast extensor digitorum longus (EDL) and slow soleus (SOL) muscles was performed and the capillary length to muscle fibre surface area ratio (Lcap/Sfib) evaluated. The Lcap/Sfib ratio of thin oxidative EDL muscle fibres was higher than that of thick glycolytic EDL muscle fibres (35,03 mm-1 ± 1,87 mm-1 : 22,28 mm-1 ± 4,04 mm-1) (p
Keywords: capillaries; muscle fibres; skeletal muscle; stereology